The Effect of Grandchildren on the Happiness of Grandparents: Does the Grandparent's Child's Gender Matter? - Eiji Yamamura; Giorgio Brunello (Institute of Labor Economics (IZA), 2021)
Using a representative sample from Japan and a difference-in-differences strategy, we investigate whether the effect of having grandchildren on the happiness of grandparents varies with the gender of their (own) single child. In line with our expectations, we find that maternal grandmothers have more to lose or less to gain from having grandchildren than paternal grandmothers. In contrast, grandfathers' changes in happiness do not depend on their own child's gender. This result is explained by the fact that grandmothers are more likely to be involved in child-rearing when their daughter has a child.
Keywords: J13; J14; J16; I31; 330; grandparents; grandchildren; happiness; gender differences